Reflecting on Inspiration and Orientation. (2nd September 2022) - Rodrigue, Michelle; Dey, Colin
ABSTRACT: In these editorial reflections, we revisit the main developments of the last year with a particular emphasis on themes of inspiration and orientation. In doing so, we pay tribute to one of SEAJ's longstanding contributors, Conny Beck, who sadly passed away at the end of last year. Then, the evolution of the sustainability accounting field leads us to revisit the current and future orientation of SEAJ, in light of its ongoing and explicit commitment to the development of a new literature in social and environmental accounting. We discuss the implications for the type of work we welcome to the journal, as well as for areas of work that are no longer compatible with the journal's aims and scope. Ultimately, we invite submitting authors to be bold, to dare, to challenge, to take us into unchartered areas. This will not only help keep SEAJ distinctive, but most importantly this is how, as a community, we will take our field further.